Is this thing on? [videorecording (DVD)] - Cooper, Bradley; Cooper, Bradley; Chappell, Mark; Bishop, John, 1966-; Arnett, Will; Arnett, Will; Dern, Laura; Day, Andra; Ebersole, Christine; Hinds, Ciarán, 1953-; Sedaris, Amy; Hayes, Sean, 1970-; et al. (Searchlight Pictures, 2026)
As their marriage unravels, Alex faces middle age and divorce, seeking new purpose in the New York comedy scene. Meanwhile, his wife Tess confronts sacrifices made for their family, forcing them to navigate co-parenting and identities.